الإجراءات الجزائية في الإمارات العربية المتحدة: الفرص والتحديات: CRIMINAL PROCEDURES IN THE UNITED ARAB EMIRATES: OPPORTUNITIES AND CHALLENGES (International Seminar on Syariah and Law (INSLA), 2020)
This study aims to identify the role of criminal procedures in the United Arab Emirates. The problem of the study lies in the existence of a state of confusion between the legal texts of each other, which may prompt the taking of penal measures that may not be commensurate with Customs crimes, as Article 7 of the Criminal Procedures Law indicated that only the Public Prosecution office has the right to take criminal measures against the accused and follow up on the progress of cases until a final judgment is issued, while Article 32 and Article 33 of the Criminal Procedures Law indicated that judicial arrest officers Of the police are authorized to take criminal measures, including collecting criminal evidence, and among government agencies other than the police, officers of the armed forces, border police, coast guards, officers of the General Administration of Residency and Foreigners Affairs, municipal inspectors, the Ministry of Health and Community Protection, and customs officials, which is a conflict between the tasks of the Public Prosecution And government agencies referred to. Article 45 indicates that it is permissible to search the accused or suspects and arrest them if there is sufficient evidence, while Article 47 states that the Public Prosecution Office alone has the power to issue decisions to search suspects, interrogate them and arrest those involved if their involvement is proven or release them if their innocence is proven. This contradicts the text of Article 5 of the Criminal Procedures Law, which states that the Public Prosecution is the one that conducts the investigation and accusation of crimes and not the judicial inspectors from other government agencies. The importance of the study was highlighted by the presence of strengthening the role of criminal procedures and the possibility of tightening those procedures in the UAE. The study followed the analytical approach to analyze the role of criminal procedures in the United Arab Emirates. The study found many results, including that the criminal procedures play a major role in achieving public restraint for not committing customs crimes in the United Arab Emirates. The study recommended the necessity of working on the classification and classification of the customs crime law to allow clarification of criminal procedures in the United Arab Emirates. تهدف هذه الدراسة إلى التعرف على دور الإجراءات الجزائية في الإمارات العربية المتحدة. وتكمن مشكلة الدراسة في وجود حالة من الالتباس بين النصوص القانونية بعضها البعض مما قد يدفع إلى اتخاذ اجراءات جزائية قد لاتتناسب مع الجرائم الجمركية، حيث أشارت المادة السابعة من قانون الإجراءات الجزائية إلى أن النيابة العامة وحدها دون غيرها هي من تملك حق اتخاذ الإجراءات الجزائية ضد المتهمين ومتابعة سير القضايا إلى حين صدور حكم نهائي في حين أشارت المادة 32  والمادة 33 من قانون الإجراءات الجزائية أن مأموري الضبط القضائي من الشرطة يصرح لها حق اتخاذ الإجراءات الجزائية بما فيها جمع الأدلة الجنائية ومن بين الجهات الحكومية الأخرى غير الشرطة ضباط القوات المسلحة وشرطة الحدود وخفر السواحل وضباط الإدارة العامة للإقامة وشئون الأجانب ومفتشو البلديات ووزارة الصحة ووقاية المجتمع وموظفو الجمارك، الأمر الذي يعد تضارباً بين مهام النيابة العامة والجهات الحكومية المشار إليها. وتشير المادة 45 انه يجوز تفتيش المتهم أو المشتبه فيهم والقبض عليهم في حالة توافر أدلة كافية في حين أن المادة 47 أقرت بأن النبابة العامة وحدها هي من تملك اصدار قرارات بتفتيش المشتبه فيهم والتحقيق معهم والقبض على المتورطين إذا ثبت تورطهم أو الافراج عنهم إذا ثبتت براءتهم، وهو ما يتعارض مع نص المادة 5 من قانون الإجراءات الجزائية التي تنص على أن النيابة العامة هي التي تباشر التحقيق والإتهام في الجرائم وليس المفتشون القضائيون من الجهات الحكومية الأخرى. وبرزت أهمية الدراسة من خلال وجود تعزيز دور الإجراءات الجزائية وإمكانية تشديد تلك الإجراءات في الإمارات العربية المتحدة. واتبعت الدراسة المنهج التحليلي لتحليل دور الإجراءات الجزائية في الإمارات العربية المتحدة. ولقد توصلت الدراسة إلى العديد من النتائج من بينها أن الإجراءات الجزائية تمارس دوراً كبيراً من أجل تحقيق الزجر العام لعدم ارتكاب الجرائم الجمركية في الإمارات العربية المتحدة. ولقد أوصت الدراسة بضرورة العمل على تبويب وتصنيف قانون الجريمة الجمركية بما يسمح من توضيح الإجراءات الجزائية في الإمارات العربية المتحدة.